Path coefficient analysis in rice cultivars - Rangel, Paulo Hideo Nakano; Galvão, José Domingos; Silva, José Carlos (Pesquisa Agropecuaria Brasileira, 2014)
In an experiment conducted at UEPAE-Manaus, state of Amazonas, the path coefficient method was applied for partitioning genotypic correlation coefficients in order to determine the direct and indirect effects of the components. Path coefficient analysis using eight characters showed that days to maturity and percentage of filled grains/panicle of rice (Oryza sativa L.) were the major characters with direct and positive influence on yield (grams/plot). The partitioning of correlation coefficients involving only primary components showed that yield of grams/plot was mainly influenced by number of spikelets/panicle and number of panicles/hill. The divergent results obtained with the two methods of analysis employed, showed that in applying path coefficient technique, selection of the characters must be done very carefully. Path analysis of the secondary versus the primary components, together with estimations of genotypic correlations showed that days to maturity and number of tillers/hill were principal indicators of the number of panicles/hill, as well as the number of spikelets/panicle and the 100 grain weight were primarily influenced by panicle length and plant height, respectively.